2000
DOI: 10.1007/bf02462611
|View full text |Cite
|
Sign up to set email alerts
|

The use of antioxidants to prevent glutamate-induced derangement of calcium ion metabolism in rat cerebral cortex synaptosomes

Abstract: Glutamate is shown to induce increases in intracellular Ca2+ concentrations ([Ca2+]i), increases in 45Ca2+ influx, decreases in the activity of Na+,K+-ATPase activity, and activation of the Na+/Ca2+ exchanger in rat cerebral cortex synaptosomes. NMDA receptor antagonists virtually prevented these effects. Preincubation of synaptosomes with alpha-tocopherol, superoxide dismutase, and ganglioside GM1 normalized [Ca2+]i, 45Ca2+ influx, and Na+,K+-ATPase activity in rat cerebral cortex synaptosomes exposed to glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…GM-1 was reported to decrease the glutamate-induced activation of free radical reactions in nerve cells, and also reduced neuronal death in a rat cerebellar granule cell culture [3,4]. These studies also revealed the antioxidant properties of ganglioside, and thus supported our present findings.…”
supporting
confidence: 91%
“…GM-1 was reported to decrease the glutamate-induced activation of free radical reactions in nerve cells, and also reduced neuronal death in a rat cerebellar granule cell culture [3,4]. These studies also revealed the antioxidant properties of ganglioside, and thus supported our present findings.…”
supporting
confidence: 91%
“…Even through the glutamate concentration reached 10 mM, both levels of AFMK still exhibited highly significant protective effects on HT22 cell viability ( Fig. 5B:KHQ+7FHOOVZHUHLQFXEDWHGZLWKDP\ORLG [25][26][27][28][29][30][31][32][33][34][35] at concentrations of 0.2, 2.0, or 2 0 FHOO YLDELOLW\ GHFUHDVHG VLJQLILFDQWO\ $0). DW WKH concentration of 1 mM significantly reduced cell death by 30% and 15% in cultured HT22 cells LQGXFHGE\0RU0DP\ORLG [25][26][27][28][29][30][31][32][33][34][35] , respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test the antioxidative ability of AFMK in cell culture further, we used three different neurotoxins to induce death of rat hippocampal neuronal cells (TH22 cell line), and also the MTT assay was used to detect cell viability because the MTT assay is a sensitive first indicator of oxidative cell damage (27). The neurotoxins were H 2 O 2 JOXWDPDWHDQGDP\ORLG [25][26][27][28][29][30][31][32][33][34][35] . H 2 O 2 is a classical oxidant, which, in high concentrations or in the presence of transition metals, triggers oxidative damage in macromolecules due to the generation of the OH (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it can induce redox-sensitive transcription factor NF-kappaB which is involved in the control of nerve cell survival [48], hence guarding against apoptosis [45]. Other studies have shown that ␣-tocopherol inhibits in vitro glutamate excitotoxicity [49,50], as well as in vivo ischemia-induced increase in glutamate [51], which could be again correlated to the free radical scavenging effect of ␣-tocopherol [51]. However, combination of ␣-tocopherol with lecithin did not affect its action.…”
Section: Discussionmentioning
confidence: 99%